Effect of fire on phosphorus forms in Sphagnum moss and peat soils of ombrotrophic bogs. (January 2015) - Wang, Guoping; Yu, Xiaofei; Bao, Kunshan; Xing, Wei; Gao, Chuanyu; Lin, Qianxin; Lu, Xianguo
Highlights: Burning converted the organic phosphorous into inorganic phosphorous. Burning steadily increased availability of inorganic phosphorus more than two times. 250 °C Burning converted most of phosphorus from the organic to the inorganic form. Fire accelerated the biogeochemical cycle of phosphorus in ombrotrophic bogs. Abstract: The effect of burning Sphagnum moss and peat on phosphorus forms was studied with controlled combustion in the laboratory. Two fire treatments, a light fire (250 °C) and a severe fire (600 °C), were performed in a muffle furnace with 1-h residence time to simulate the effects of different forest fire conditions. The results showed that fire burning Sphagnum moss and peat soils resulted in losses of organic phosphorus (Po ), while inorganic phosphorus (Pi ) concentrations increased. Burning significantly changed detailed phosphorus composition and availability, with severe fires destroying over 90% of organic phosphorus and increasing the availability of inorganic P by more than twofold. Our study suggest that, while decomposition processes in ombrotrophic bogs occur very slowly, rapid changes in the form and availability of phosphorus in vegetation and litter may occur as the result of forest fires on peat soils.